PENGARUH PERAN PENYULUH PERTANIAN TERHADAP PERILAKU PETANI KAKAO (Theobroma cacao L) DI KELOMPOK TANI METEN LER DESA BLORO KECAMATAN NITA KABUPATEN SIKKA - Yosefa Rensiana, Agustina; Noni, Sarlina; Yakob Da Rato, Yoseph Yakob Da Rato (Universitas Cokroaminoto Palopo, 2024)
Agricultural extension workers are individuals engaged in the agricultural sector with highly significant responsibilities for farmers and farmer groups. Their role involves providing guidance and motivation to help farmers enhance their ability to manage natural resources, increase knowledge, and develop skills to foster behavioral change. The purpose of this study is to analyze the influence of the role of agricultural extension workers on the behavior of cocoa farmers in the Meten Ler Farmer Group, Bloro Village, Nita Subdistrict, Sikka Regency. Based on the research conducted on the Meten Ler Farmer Group, the study concludes that the role of agricultural extension workers has a positive influence on farmers' behavior. This means that improvements in the effectiveness of extension workers' roles lead to enhanced effectiveness in farmers' behavioral performance. This finding is supported by a significance value (sig.) smaller than the alpha value, i.e., 0.000 < 0.05, indicating that the role of extension workers has a positive and significant impact on farmers' behavior. Furthermore, the t-value (t calculated) exceeds the t-table value (2.4229 > 1.697), resulting in the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (Ha). This demonstrates that the role of extension workers within the Meten Ler Farmer Group has a positive and significant impact on farmers' behavior.